Composite solid electrolyte and all-solid-state battery comprising same

By forming a polymer coating with a viscosity of 30 to 110 Mooneyne on the sulfide-based solid electrolyte, the problem of strong reactivity of sulfide-based electrolytes to moisture is solved, the atmospheric stability and chemical resistance are improved, and the toxicity is reduced The gas produces and maintains high ionic conductivity.

CN119301790APending Publication Date: 2025-01-10LG CHEM LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046374.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-07-04
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The sulfide-based solid electrolyte is highly reactive to moisture, leading to the production of harmful gas hydrogen sulfide, affecting workers' safety and reducing battery performance.

Method used

A polymer coating with a viscosity of 30 to 110 Mooney is used to cover sulfide-based solid electrolyte particles to form a composite solid electrolyte to enhance its atmospheric stability and chemical resistance.

Benefits of technology

Effectively prevent the decomposition and deterioration of sulfide-based solid electrolytes in moisture or oxygen, reduce the production of toxic gas hydrogen sulfide, maintain high ion conductivity, and improve the chemical resistance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The present invention aims to improve the atmospheric stability of a conventional sulfide-based solid electrolyte, and relates to a composite solid electrolyte and an all-solid-state battery comprising the same, the composite solid electrolyte comprising: sulfide-based solid electrolyte particles; and a polymer coating layer formed on the sulfide-based solid electrolyte particles, the polymer coating layer including a polymer having a Mooney viscosity (ML1 + 4, 100 DEG C) in the range of 30 to 110.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0082075 filed on July 4, 2022, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to a sulfide-based composite solid electrolyte having improved atmospheric stability and chemical resistance, and an all-solid-state battery comprising the sulfide-based composite solid electrolyte. Background Art

[0004] All-solid-state batteries are batteries that are configured to replace the liquid electrolyte filled between the positive and negative electrodes of typical lithium secondary batteries with solid electrolytes. They are safe and have no risk of explosion, and have higher energy density than typical batteries, so they are considered to be the preferred choice for the next generation of batteries. The solid electrolyte used in all-solid-state batteries is a solid material that can conduct lithium ions in the battery and has an ion conductivity as high as that of the electrolyte currently used in lithium secondary batteries. The core materials that make up the solid electrolyte include polymers, sulfides, and oxides, but in particular, sulfide-based solid electrolytes with large ductility and high ion conductivity are considered to be suitable for making large-size, high-capacity batteries.

[0005] However, a limitation of sulfide-based solid electrolytes is that the electrolyte is highly reactive to moisture, and therefore reacts not only with moisture in the air but also with moisture at low humidity to produce harmful gas hydrogen sulfide (H2S). As a result, the toxic hydrogen sulfide has an adverse effect on worker safety and deteriorates the performance of the sulfide-based solid electrolyte itself.

[0006] Therefore, there is still a need to develop sulfide-based solid electrolytes with excellent atmospheric stability and chemical resistance. Summary of the invention

[0007] Technical issues

[0008] One aspect of the present invention provides a composite solid electrolyte having improved atmospheric stability and chemical resistance.

[0009] However, the objects of the present invention are not limited to the above, and those skilled in the art will clearly understand other objects not described herein from the following description.

[0010] Technical Solution

[0011] In order to solve the above problems, the present invention provides a composite solid electrolyte and an all-solid-state battery.

[0012] According to one aspect of the present invention, a composite solid electrolyte is provided, which comprises sulfide-based solid electrolyte particles; and a polymer coating, wherein the polymer coating is formed on the sulfide-based solid electrolyte particles, wherein the polymer coating comprises a polymer having a Mooney viscosity (ML1+4, 100°C) of 30 to 110.

[0013] The present invention provides the composite solid electrolyte according to (1) above, wherein the sulfide-based solid electrolyte has an argyrodite-type crystal structure.

[0014] The present invention provides a composite solid electrolyte according to (1) or (2) above, wherein the polymer of the polymer coating is at least one selected from the group consisting of: polymers of acrylonitrile monomers and butadiene monomers, their hydrides, and polymers of styrene monomers and butadiene monomers.

[0015] The present invention provides a composite solid electrolyte according to any one of (1) to (3) above, wherein the polymer of the polymer coating layer comprises a repeating unit represented by the following Formula 1 and a repeating unit represented by the following Formula 2.

[0016] [Formula 1]

[0017]

[0018] [Formula 2]

[0019] .

[0020] (5) The present invention provides a composite solid electrolyte according to any one of (1) to (4) above, wherein the polymer of the polymer coating layer contains a repeating unit derived from an acrylonitrile monomer in an amount of 15 wt % to 50 wt % relative to the total weight of the polymer.

[0021] (6) The present invention provides a composite solid electrolyte according to any one of (1) to (5) above, wherein the polymer of the polymer coating layer contains a repeating unit derived from a butadiene monomer in an amount of 50 wt % to 85 wt % relative to the total weight of the polymer.

[0022] (7) The present invention provides a composite solid electrolyte according to any one of (1) to (6) above, wherein the composite solid electrolyte contains 0.1 to 10 parts by weight of the polymer coating relative to 100 parts by weight of the sulfide-based solid electrolyte particles.

[0023] (8) The present invention provides the composite solid electrolyte according to any one of (1) to (7) above, wherein the composite solid electrolyte has an ion conductivity of 0.001 mS / cm to 20 mS / cm.

[0024] (9) The present invention provides a composite solid electrolyte according to any one of (1) to (8) above, wherein when the composite solid electrolyte is exposed to a temperature of 25° C. and a relative humidity of 0.5% to 0.6%, the amount of hydrogen sulfide (H2S) generated during the first hour is 15 cm3 / g of the composite solid electrolyte. 3 the following.

[0025] (10) According to another aspect of the present invention, there is provided an all-solid-state battery comprising the composite solid electrolyte according to any one of (1) to (9) above.

[0026] Beneficial Effects

[0027] The composite solid electrolyte according to the present invention has a polymer coating having excellent atmospheric stability and chemical resistance formed on sulfide-based solid electrolyte particles, so the composite solid electrolyte itself can have excellent atmospheric stability and improved chemical resistance in a wet process for manufacturing a battery. DETAILED DESCRIPTION

[0028] Hereinafter, the present invention will be described in detail to help understanding of the present invention.

[0029] It should be understood that the words or terms used in this document should not be interpreted as the meanings defined in commonly used dictionaries, and it should also be understood that, based on the principle that the inventor can appropriately define the meanings of the words or terms to best explain the present invention, the words or terms should be interpreted as having a meaning consistent with their meanings in the context of the relevant art and the technical idea of ​​the present invention.

[0030] The terminology used herein is for the purpose of describing particular example embodiments only and is not intended to be limiting of the present invention.Singular forms are intended to include plural forms as well, unless the context clearly indicates otherwise.

[0031] It should also be understood that the terms “comprises,” “comprising,” or “having” when used in this specification specify the presence of stated features, numbers, steps, elements, or a combination thereof, but do not preclude the presence or addition of one or more other features, numbers, steps, elements, or a combination thereof.

[0032] In this article, Mooney viscosity is a value measured using a Mooney viscometer, and is specifically measured in the following manner: a sample is placed on a rotor of a lower mold set in the Mooney viscometer, an upper mold is lowered under a constant piston pressure (about 70 psi), and then the mold is preheated for 1 minute at an internal temperature of 100°C of the testing machine mold, the mold is rotated clockwise for 4 minutes at a rate of 2 rpm, and the torque applied to the rotor is measured, and the Mooney viscosity in this article is the value of the torque measured after 1 minute of preheating (including the preheating time for a total of 5 minutes). In this article, the measurement conditions for Mooney viscosity are expressed as (ML1+4, 100°C), and M is an abbreviation for Mooney viscosity, L is an abbreviation for large rotor, the number 1 indicates the preheating time, +4 indicates the rotation time of the rotor, and 100°C indicates the measurement temperature.

[0033] Composite solid electrolyte

[0034] The composite solid electrolyte according to the present invention includes sulfide-based solid electrolyte particles and a polymer coating layer formed on the sulfide-based solid electrolyte particles, and the polymer coating layer includes a polymer having a Mooney viscosity (ML1+4, 100° C.) of 30 to 110.

[0035] The inventors of the present invention have found that the composite solid electrolyte according to the present invention has a polymer coating with excellent atmospheric stability (good moisture and oxygen barrier properties) formed on sulfide-based solid electrolyte particles, so that the composite solid electrolyte itself can have excellent atmospheric stability and improved chemical resistance in dry and wet processes for manufacturing batteries, thereby achieving the present invention.

[0036] In the composite solid electrolyte according to the present invention, the polymer coating contains a polymer having a Mooney viscosity (ML1+4, 100°C) of 30 to 110, and thus, the sulfide-based solid electrolyte particles can be prevented from decomposing and deteriorating when exposed to moisture or oxygen. Therefore, the generation of toxic gas hydrogen sulfide can be prevented, and the ion conductivity of the composite solid electrolyte can be prevented from decreasing. The polymer may have a Mooney viscosity (ML1+4, 100°C) of specifically 30 to 90, more specifically 30 to 80. On the other hand, when the polymer has a Mooney viscosity of less than 30, heat resistance and chemical resistance are reduced, resulting in instability when driving the battery; and when the polymer has a Mooney viscosity greater than 110, the coating is formed thick and uneven, resulting in low ion conductivity and insufficient moisture blocking effect.

[0037] According to the present invention, the sulfide-based solid electrolyte may have an argyrodite-type crystal structure in terms of high ion conductivity and low reactivity with a lithium negative electrode. The sulfide-based solid electrolyte may be a sulfide-based solid electrolyte containing Li, P, and S. For example, the sulfide-based solid electrolyte may be Li 7-x PS 6-x A x (wherein A is Cl, Br, I, Sn or a combination thereof, and x satisfies 0≤x≤2).

[0038] According to the present invention, the polymer of the polymer coating layer may be at least one selected from the group consisting of: a polymer of acrylonitrile monomer and butadiene monomer, its hydride, and a polymer of styrene monomer and butadiene monomer. That is, the polymer of the polymer coating layer may be at least one selected from the group consisting of: acrylonitrile-butadiene resin as a copolymer of acrylonitrile monomer and butadiene monomer, hydrogenated acrylonitrile-butadiene resin as its hydride, and styrene-butadiene resin as a copolymer of styrene monomer and butadiene monomer. In this case, it is beneficial that the composite solid electrolyte particles have improved dispersibility in the electrode slurry process due to the similarity with the binder material.

[0039] According to the present invention, in terms of improving the dispersibility of the composite solid electrolyte particles in an electrode slurry process, the polymer of the polymer coating layer may include a repeating unit represented by the following Formula 1 and a repeating unit represented by the following Formula 2.

[0040] [Formula 1]

[0041]

[0042] [Formula 2]

[0043] .

[0044] According to the present invention, the polymer of the polymer coating layer may contain repeating units derived from acrylonitrile monomers at 15 to 50 wt %, specifically 20 to 40 wt %, relative to the total weight of the polymer. In this case, the dispersibility of the composite solid electrolyte particles is improved and they are easily dissolved in a non-polar solvent used to prepare a coating solution.

[0045] According to the present invention, the polymer of the polymer coating layer may contain a repeating unit derived from a butadiene monomer at 50 to 85 wt %, specifically 60 to 80 wt %, relative to the total weight of the polymer.

[0046] For example, when the polymer of the polymer coating layer is formed by a repeating unit represented by Formula 1 above and a repeating unit represented by Formula 2 above, the content of the repeating unit represented by Formula 1 above may be 15 wt % to 50 wt %, and the content of the repeating unit represented by Formula 2 above may be 50 wt % to 85 wt %, relative to the total weight of the polymer.

[0047] According to the present invention, the content of the polymer coating layer may be 0.1 to 10 parts by weight, specifically 0.1 to 7 parts by weight, and more specifically 0.5 to 5 parts by weight, relative to 100 parts by weight of the sulfide-based solid electrolyte particles. In this case, the moisture blocking effect can be improved and the reduction in ion conductivity can be minimized.

[0048] According to the present invention, the composite solid electrolyte may have an ion conductivity of 0.001 mS / cm or more, specifically 0.001 mS / cm to 20 mS / cm, more specifically 0.01 mS / cm to 10 mS / cm or 0.01 mS / cm to 5 mS / cm. The higher the ion conductivity of the electrolyte, the better, but when the polymer coating is formed so that the ion conductivity satisfies the above range as in the present invention, the moisture stability effect can be improved.

[0049] According to the present invention, when the composite solid electrolyte is exposed to a temperature of 25° C. and a relative humidity of 0.5% to 0.6%, during the first hour, the amount of hydrogen sulfide (H2S) produced may be 15 cm3 / g of the composite solid electrolyte. 3 Below, or specifically 14 cm 3 Below. That is, the composite solid electrolyte according to the present invention has excellent moisture stability, and therefore can have a low ion conductivity reduction rate even after exposure to moisture, and has a low amount and rate of generation of hydrogen sulfide (toxic gas), thereby obtaining process safety. On the other hand, the atmosphere when the composite solid electrolyte is exposed to a temperature of 25° C. and a relative humidity of 0.5% to 0.6% can be an air atmosphere.

[0050] The composite solid electrolyte according to the present invention may be manufactured by coating sulfide-based solid electrolyte particles with a polymer composition including a polymer having a Mooney viscosity (ML1+4, 100° C.) of 30 to 110.

[0051] The sulfide-based solid electrolyte particles can be synthesized, for example, by mechanical grinding. Specifically, three types of precursors Li2S, P2S5 and LiCl are weighed according to stoichiometry and then mixed by ball milling. The obtained mixed precursor is heat treated for crystallization and then crushed again by ball milling. The mixing, heat treatment and crushing steps are performed in an inert gas atmosphere.

[0052] The polymer having a Mooney viscosity (ML1+4, 100° C.) of 30 to 110 can be prepared by polymerizing the acrylonitrile monomer and the butadiene monomer by a method such as suspension polymerization, solution polymerization, and bulk polymerization. For example, the polymer can be prepared by dispersing the acrylonitrile monomer and the butadiene monomer, an optional chain transfer agent, a dispersant, a thermal initiator, etc. in a solvent, then performing suspension polymerization and mixing the materials with a stirrer.

[0053] In addition, the polymer composition may be prepared by dissolving or dispersing a polymer having a Mooney viscosity (ML1+4, 100° C.) of 30 to 110 in a solvent such as toluene or xylene. In this case, the weight ratio of the polymer having a Mooney viscosity (ML1+4, 100° C.) of 30 to 110 to the solvent such as toluene or xylene may be 1:20 to 2:1.

[0054] Finally, coating can be performed by mixing and stirring the polymer composition and the sulfide-based solid electrolyte and then drying the resulting product, or spraying the polymer composition onto the sulfide-based solid electrolyte and then drying the resulting product. However, the present invention is not limited thereto and can be performed by methods known in the art.

[0055] All-solid-state battery

[0056] The present invention provides an all-solid-state battery comprising the composite solid electrolyte.

[0057] Specifically, the all-solid-state battery includes: a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and a solid electrolyte layer containing the composite solid electrolyte according to the present invention disposed between the positive electrode and the negative electrode.

[0058] The all-solid-state battery according to the present invention has a small decrease in ion conductivity due to moisture, and thus can have excellent initial efficiency, life characteristics, and output characteristics.

[0059] In this case, the all-solid-state battery of the present invention can be manufactured according to typical methods known in the art. For example, the all-solid-state battery of the present invention can be manufactured by the following method: stacking and pressing are carried out to place a solid electrolyte layer between the positive electrode and the negative electrode.

[0060] (1) Positive electrode

[0061] The positive electrode can be prepared by coating a positive electrode current collector with a positive electrode paste containing a positive electrode active material, a binder, a conductive agent, a solvent, etc.

[0062] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. Fine irregularities can be formed on the surface of the positive electrode current collector to improve the adhesion of the positive electrode active material, and the positive electrode current collector can have various forms, such as a film, a sheet, a foil, a net, a porous body, a foam body, and a non-woven fabric body.

[0063] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium, and the positive electrode active material can specifically contain a lithium metal oxide containing lithium and at least one metal such as cobalt, manganese, nickel, or aluminum. More specifically, the lithium metal oxide can include lithium-manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (e.g., LiCoO2, etc.), lithium-nickel-based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese-based oxides (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), lithium-nickel-cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), lithium-manganese-cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-z1 Co z1 O4 (where 0 < Z1 < 2), etc.), lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, and p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2)O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, and p1 + q1 + r2 = 2, etc.) or lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r3 M S2 )O2 (where M is selected from the group consisting of aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg), and molybdenum (Mo), and p2, q2, r3, and s2 are each the atomic fraction of an independent element, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, and p2 + q2 + r3 + s2 = 1), and may include any one or a mixture of two or more thereof.

[0064] Among the compounds listed above, in terms of improving the capacity characteristics and stability of the battery, the lithium composite metal oxide may include LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2) or lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), and, considering the significant improvement due to controlling the type and content ratio of the elements constituting the lithium composite metal oxide, the lithium composite metal oxide may include Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, and any one or a mixture of two or more thereof may be used.

[0065] The positive electrode active material may be contained in an amount of 60 to 99 wt %, preferably 70 to 99 wt %, and more preferably 80 to 98 wt % relative to the total weight of the solid content (excluding the solvent) of the positive electrode slurry.

[0066] The binder is a component that helps the conductive agent, the active material and the current collector to adhere to each other. Examples of such binders may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber and various copolymers thereof.

[0067] Generally, the binder may be contained in an amount of 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt % relative to the total weight of the solid content (excluding the solvent) of the positive electrode slurry.

[0068] The conductive agent is a component for further improving the conductivity of the positive electrode active material.

[0069] Any conductive agent can be used without particular limitation as long as it has conductivity and does not cause chemical changes in the battery, and for example, conductive materials such as graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as fluorocarbon powder, aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.

[0070] The content of the conductive agent may be generally 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt % relative to the total weight of the solid content (excluding the solvent) of the positive electrode slurry.

[0071] The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that a desired viscosity is obtained when the positive electrode active material, the optional binder and the conductive agent are included. For example, the content of the solvent may be such that the concentration of the solid component containing the positive electrode active material and the optional binder and the conductive agent may be 50% to 95% by weight, preferably 70% to 95% by weight, and more preferably 70% to 90% by weight.

[0072] (2) Negative electrode

[0073] The negative electrode may be prepared by coating a negative electrode current collector with a negative electrode slurry including a negative electrode active material, a binder, a conductive agent, and a solvent, or a graphite electrode made of carbon (C) or metal itself may be used as the negative electrode.

[0074] For example, the negative electrode current collector is coated with the negative electrode slurry to manufacture the negative electrode, and the negative electrode current collector generally has a thickness of 3 to 500 μm. The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, as in the positive electrode current collector, the negative electrode current collector may have fine concave-convex on its surface to improve the bonding strength of the negative electrode active material, and the negative electrode current collector may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0075] The negative electrode active material may be, for example, one or at least two selected from the group consisting of natural graphite, artificial graphite, carbonaceous materials; lithium-containing titanium composite oxide (LTO), metal (Me): Si, SiO x , Sn, Li, Zn, Mg, Cd, Ce, Ni or Fe; alloys formed by metal (Me); oxides (MeO x ); and a composite of metal (Me) and carbon. The negative electrode active material may specifically contain silicon (Si), silicon oxide (SiO x ) or a silicon-based negative electrode active material of a silicon alloy. In this case, a thin and stable SEI layer containing a siloxane bond is formed, so the battery can have further improved high temperature stability and life characteristics.

[0076] The negative electrode active material may be contained in an amount of 60 to 99 wt %, preferably 70 to 99 wt %, and more preferably 80 to 98 wt % relative to the total weight of the solid content (excluding the solvent) of the negative electrode slurry.

[0077] The binder is a component that helps the conductive agent, the active material and the current collector to adhere to each other. Examples of the binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber and various copolymers thereof.

[0078] Generally, the binder may be contained in an amount of 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt % relative to the total weight of the solid content (excluding the solvent) of the negative electrode slurry.

[0079] The conductive agent is a component for further improving the conductivity of the negative electrode active material. Such conductive agents are not particularly limited as long as they have conductivity and do not cause chemical changes in the battery, and can be, for example, graphite, such as natural graphite and artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; metal powders, such as fluorocarbon powder, aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives, etc.

[0080] The conductive agent may be contained in an amount of 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt % relative to the total weight of the solid content (excluding the solvent) of the negative electrode slurry.

[0081] The solvent may include water or an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount such that a desired viscosity is obtained when the negative electrode active material, the optional binder and the conductive agent are included. For example, the content of the solvent may be such that the concentration of the solid component containing the negative electrode active material and the optional binder and the conductive agent may be 50% to 95% by weight, and preferably 70% to 90% by weight.

[0082] When a metal itself is used as the negative electrode, the negative electrode may be formed of a metal thin film itself, or may be prepared by physically bonding, rolling or vapor-depositing the metal on the negative electrode current collector. Electrodeposition or chemical vapor deposition may be used as a deposition technique.

[0083] For example, the metal thin film itself or the metal formed by bonding / rolling / deposition on the negative electrode current collector may include one or an alloy of two metals selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In).

[0084] (3) Solid electrolyte layer

[0085] The solid electrolyte layer may further contain a binder in addition to the solid electrolyte according to the present invention.

[0086] The binder is a component that helps the conductive agent, the active material and the current collector to adhere to each other. Examples of such binders may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber and various copolymers thereof.

[0087] The content of the binder may be generally 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt % relative to the total weight of the solid electrolyte layer.

[0088] The present invention provides a battery module including the all-solid-state battery as a unit cell and a battery pack including the all-solid-state battery. The battery module and the battery pack include secondary batteries having high capacity, high rate characteristics and cycle characteristics, and can therefore be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0089] Mode for carrying out the invention

[0090] Hereinafter, preferred embodiments are provided to help understand the present invention, but the embodiments are only used to illustrate the present description, and it will be obvious to those skilled in the art that various modifications and changes are possible within the scope and technical scope of the present invention, and such modifications and changes fall within the scope of the claims included herein.

[0091] Preparation Example

[0092] The three types of precursors Li2S, P2S5 and LiCl were dry mixed (ball milled) at a molar ratio of 5:1:2. In the dry mixing, a planetary ball mill equipped with zirconia balls was used and rotated at a rate of more than 300 rpm for uniform mixing. Thereafter, the obtained mixed precursor was heat treated at 600°C for 12 hours for crystallization, and then pulverized by ball milling again to prepare Li6PS5Cl having a argyrodite-type crystal structure. All of the above processes were carried out in an inert Ar atmosphere.

[0093] Examples and Comparative Examples

[0094] Example 1

[0095] A polymer composition was prepared by dissolving 5 parts by weight of a polymer having a Mooney viscosity of 35 relative to 100 parts by weight of xylene. In this case, the polymer contained 33.0% by weight of a repeating unit derived from an acrylonitrile monomer relative to the total weight of the polymer.

[0096] The polymer composition and Li6PS5Cl having an argyrodite type crystal structure were mixed in a weight ratio of 1:1 and stirred using a stirrer for 1 hour, and then the solvent was removed by vacuum drying to form a polymer coating on Li6PS5Cl particles having an argyrodite type crystal structure.

[0097] As a result, a composite solid electrolyte was obtained in which the polymer coating layer containing the polymer having a Mooney viscosity of 35 was formed on Li6PS5Cl particles having an argyrodite type crystal structure. In this case, the polymer coating layer was present in an amount of 4.76 parts by weight relative to 100 parts by weight of Li6PS5Cl.

[0098] Example 2

[0099] A composite solid electrolyte was obtained in the same manner as in Example 1, wherein a polymer coating containing a polymer having a Mooney viscosity of 46 was formed on Li6PS5Cl particles having an argyrodite-type crystal structure, except that a polymer having a Mooney viscosity of 46 and containing 33.5 wt % of repeating units derived from acrylonitrile monomer relative to the total weight of the polymer was used.

[0100] Example 3

[0101] A composite solid electrolyte was obtained in the same manner as in Example 1, wherein a polymer coating containing a polymer having a Mooney viscosity of 77.5 was formed on Li6PS5Cl particles having an argyrodite-type crystal structure, except that a polymer having a Mooney viscosity of 77.5 and containing 33.5 wt % of repeating units derived from acrylonitrile monomer relative to the total weight of the polymer was used.

[0102] Comparative Example 1

[0103] In Comparative Example 1, Li6PS5Cl having an argyrodite-type crystal structure prepared in Preparation Example was used as a solid electrolyte.

[0104] Comparative Example 2

[0105] A composite solid electrolyte was obtained in the same manner as in Example 1, wherein a polymer coating containing a polymer having a Mooney viscosity of 27 was formed on Li6PS5Cl particles having an argyrodite-type crystal structure, except that a polymer having a Mooney viscosity of 27 and containing 33.5 wt % of repeating units derived from acrylonitrile monomer relative to the total weight of the polymer was used.

[0106] Comparative Example 3

[0107] The composite solid electrolyte is obtained in the same manner as in Example 1, wherein a polymer coating containing a polymer having a Mooney viscosity of 115 is formed on Li6PS5Cl particles having an argyrodite-type crystal structure, except that a polymer having a Mooney viscosity of 115 and containing 33.5 wt % of repeating units derived from acrylonitrile monomer relative to the total weight of the polymer is used.

[0108]

[0109] Experimental Example 1: Evaluation of ion conductivity

[0110] 150 mg of each composite solid electrolyte of Examples 1 to 3, the solid electrolyte of Comparative Example 1, and the composite solid electrolyte powder of Comparative Examples 2 and 3 were placed in a SUS mold with a diameter of 13 mm. The mold was mounted on a press together with PEEK for insulation, and a constant potential instrument was connected to the SUS mold. After the electrolyte structure was fully densified under a pressure of 370 MPa, the pressure was slowly reduced and maintained at 100 MPa, and the AC impedance was measured at a measurement frequency of 1 Hz to 7 MHz. The ionic conductivity was calculated from the measured resistance value by the Nyquist plot, and the results are shown in Table 2 below. All measurements were carried out in a drying chamber at a temperature of 25 ° C and a relative humidity of 0.59%.

[0111] Experimental Example 2: Evaluation of Hydrogen Sulfide Gas Generation

[0112] 5 mg each of the composite solid electrolytes of Examples 1 to 3, the solid electrolyte of Comparative Example 1, and the composite solid electrolyte powders of Comparative Examples 2 and 3 were each placed in a glove box equipped with a hydrogen sulfide sensor (in a dry air atmosphere controlled to have a relative humidity of 0.59%) for 1 hour or more. Immediately after the placement, the amount of hydrogen sulfide generated per 1 g of the composite solid electrolyte was calculated from the amount of hydrogen sulfide generated within 1 hour, and the results are shown in Table 2 below.

[0113]

[0114] Referring to Table 2, it can be seen that the hydrogen sulfide gas generated in the composite solid electrolytes of Examples 1 to 3 is less than that in the solid electrolytes of Comparative Examples 1 to 3, which indicates that the composite solid electrolytes of Examples 1 to 3 have excellent atmospheric stability and chemical resistance. The polymer used in the polymer coating of Examples 1 to 3 acts as a resistor, so it can be seen that the composite solid electrolytes of Examples 1 to 3 have lower ion conductivity than Comparative Examples 1 and 2, but have significantly better moisture barrier properties.

[0115] As a result, it can be seen that in the composite solid electrolyte according to the present invention, the polymer coating layer contains a polymer having a Mooney viscosity (ML1+4, 100°C) of 30 to 110, and therefore, the sulfide-based solid electrolyte particles can be prevented from decomposing and deteriorating when exposed to moisture or oxygen. Therefore, it can be seen that the generation of toxic gas hydrogen sulfide can be prevented, and the ion conductivity of the composite solid electrolyte can be prevented from decreasing.

Claims

1. A composite solid electrolyte comprising: Sulfide-based solid electrolyte particles; and a polymer coating layer formed on the sulfide-based solid electrolyte particles, in, The polymer coating comprises a polymer having a Mooney viscosity (ML1+4, 100° C.) of 30 to 110. 2 . The composite solid electrolyte according to claim 1 , wherein the sulfide-based solid electrolyte has an argyrodite-type crystal structure.

3. The composite solid electrolyte according to claim 1, wherein the polymer of the polymer coating is at least one selected from the group consisting of: Polymers of acrylonitrile and butadiene, their hydrides, and polymers of styrene and butadiene.

4. The composite solid electrolyte according to claim 1, wherein the polymer of the polymer coating layer comprises a repeating unit represented by the following formula 1 and a repeating unit represented by the following formula 2: [Formula 1] [Formula 2] 。 5 . The composite solid electrolyte according to claim 1 , wherein the polymer of the polymer coating layer comprises a repeating unit derived from an acrylonitrile monomer in an amount of 15 wt % to 50 wt % relative to the total weight of the polymer. 6 . The composite solid electrolyte according to claim 1 , wherein the polymer of the polymer coating layer comprises a repeating unit derived from a butadiene monomer in an amount of 50 wt % to 85 wt % relative to the total weight of the polymer. 7 . The composite solid electrolyte according to claim 1 , wherein the composite solid electrolyte comprises 0.1 to 10 parts by weight of the polymer coating layer relative to 100 parts by weight of the sulfide-based solid electrolyte particles. 8 . The composite solid electrolyte according to claim 1 , wherein the composite solid electrolyte has an ion conductivity of 0.001 to 20 mS / cm.

9. The composite solid electrolyte according to claim 1, wherein when the composite solid electrolyte is exposed to a temperature of 25° C. and a relative humidity of 0.5% to 0.6%, the amount of hydrogen sulfide (H2S) produced during the first hour is 15 cm3 / g of the composite solid electrolyte. 3 the following.

10. An all-solid-state battery comprising the composite solid electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Fingerprint detection system

    KR1020220082075A